Data‐Driven Kinematic Control for Robotic Spatial Augmented Reality System with Loose Kinematic Specifications - Lee, Ahyun; Lee, Joo‐Haeng; Kim, Jaehong (ETRI journal, 2016)
We propose a data‐driven kinematic control method for a robotic spatial augmented reality (RSAR) system. We assume a scenario where a robotic device and a projector‐camera unit (PCU) are assembled in an ad hoc manner with loose kinematic specifications, which hinders the application of a conventional kinematic control method based on the exact link and joint specifications. In the proposed method, the kinematic relation between a PCU and joints is represented as a set of B‐spline surfaces based on sample data rather than analytic or differential equations. The sampling process, which automatically records the values of joint angles and the corresponding external parameters of a PCU, is performed as an off‐line process when an RSAR system is installed. In an on‐line process, an external parameter of a PCU at a certain joint configuration, which is directly readable from motors, can be computed by evaluating the pre‐built B‐spline surfaces. We provide details of the proposed method and validate the model through a comparison with an analytic RSAR model with synthetic noises to simulate assembly errors.